The improvement of the efficiency of fertilizers’ use for spring barley sowings - E. N. Fedotova; Yu. N. Fedorova; D. S. Komshanov (Зерновое хозяйство России, 2018)
The improvement of the efficiency of fertilizers’ use for spring barley sowings According to three-year long researches and farming tests the article presents the efficiency of fertilizers’ use combined with the compound microelement fertilizer “Akvadon-Mikro”. The principle effect of microelements and their use with mineral fertilizers upon increase of barley productivity has been established. On average the grain productivity was 2.25 t/ha on the control variant. While using mineral fertilizers (in proportion of N40P60K90) the yield increased on 0.73 t/ha with the payback of 1 kg of NPK equal to 3.9 kg of grain. The use of the fertilizer “Akvadon-Mikro” increased the productivity up to 0.98 t/ha, with the payback of 1 kg of NPK equal to 5.2 kg of grain. The use of the fertilizer in proportion of N28P40K60 increased the productivity on 0.99 t/ha with the payback of 1 kg of NPK equal to 7.8 kg of grain. The farming experiments showed that the use of the fertilizer in a reduced to N28P40K60 proportion combined with the microelement fertilizer “Akvadon-Mikro” produced the largest yield of grain (3.89 t/ha), that is on 1.91 t/ha more than that of the control variant. The use of the fertilizers with this microfertilizer increased the profit per hectare on 31 745 rb and on 803.7 rb per 1 hwt of barley, if the fertilizer was used in proportion N40P60K90. The profitability has increased on 61% compared with the control variant and it is 161.9%. When the fertilizer was used in proportion N28P40K60, the profit per hectare increased on 32 286 rb and on 830 rb per 1 hwt of barley. The profitability has increased on 75.7% compared with the control variant and it is 176.6%. The study showed, the use of microfertilizers has become an important factor of barley productivity increase, providing reliable yields. On average during the years of study the efficiency of a combined use of microelements and mineral fertilizers was the same. Due to better assimilation of nutrients, the use of a microelement fertilizer increased productivity on the areas with various fertilizing, which made it possible to reduce the dosage of mineral fertilizers.